PENGARUH PELABURAN AMONIUM HIDROKSIDA TERHADAP EMISI FORMALDEHIDA KAYU LAPIS DAN PAPAN PARTIKEL - Adi Santoso; Adi Yuwono; A. R. M. Renwarin; Paribotro Sutigno (Universitas Nusa Bangsa, 2011)
The effect of spreading by ammonium hydroxide on formaldehyde emission of plywood and particleboardThe formaldehyde emmision from panel products such as plywood and particleboard bonded with urea formaldehyde (UF) can have negative effects to human health, especially if used in a room with limited ventilation. To reduce formaldehyde emission, chemical agents can be applied to the product. In this exsperiment report, the effect of ammonium hydroxide 25% application on formaldehyde emission of UF on to wards the bonded plywood and particleboard was described. Application of ammonium hydroxide on plywood and particleboard significantly affected UF emission. The higher amount of application of ammonium hydroxide, the lower formaldehyde emission from plywod and particleboard. The effect of ammonium hydroxide to UF emission level differed according to type of panel and examination standard. Application of ammonium hydroxide of 0.009 ml/cm2 and 0.015 ml/cm2, the formaldehyde emission of plywood and particleboard could meet Japanese Standard; while spreading on particleboard of 0,003 ml/cm2and on plywood of 0,014 ml/cm2, the formaldehyde emission could conform to American Standard.Key words : Plywood, particleboard, formaldehyde emission, spreading, ammonium hydroxide ABSTRAKEmisi formaldehida dari produk panel seperti kayu lapis dan papan partikel yang direkat dengan urea formaldehida (UF) dapat mengganggu kesehatan, terutama jika digunakan di dalam ruangan dengan ventilasi terbatas. Untuk mengurangi emisi formal-dehida, produk tersebut dapat dilburi dengan suatu bahan kimia. Dalam tulisan ini dikemukakan pengaruh dari penggunaan pelaburan dengan amonium hidroksida 25 % terhadap emisi formaldehida kayu lapis dan papan partikel yang masing-masing direkat dengan UF. Pengaruh pelaburan dengan amonium hidroksida terhadap emisi formaldehida kayu lapis dan papan partikel masing-masing sangat nyata. Semakin banyak amonium hidroksida yang dilaburkan, emisi formaldehida dari kayu lapis dan papan partikel sema-kin rendah. Pengaruh amonium hidroksida terhadap tingkat penurunan emisi formaldehida berbeda menurut jenis panel dan standar pengujian. Pada pelaburan dengan amonium hidroksida sebanyak 0,009 ml/cm2 dan 0,015 ml/cm2, kayu lapis dan papan partikel memenuhi persyaratan emisi formaldehida Standar Jepang. Sedangkan pelaburan pada papan partikel sebanyak 0,003 ml/cm2, dan pada kayu lapis sebanyak 0,014 ml/cm2, emisi formaldehidanya memenuhi Standar Amerika.Kata kunci : Kayu lapis, papan partikel, emisi formaldehida, pelaburan, amonium hidroksida